2013
DOI: 10.1172/jci65538
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic glucose sensing is required to preserve β cell glucose competence

Abstract: Liver glucose metabolism plays a central role in glucose homeostasis and may also regulate feeding and energy expenditure. Here we assessed the impact of glucose transporter 2 (Glut2) gene inactivation in adult mouse liver (LG2KO mice). Loss of Glut2 suppressed hepatic glucose uptake but not glucose output. In the fasted state, expression of carbohydrate-responsive element-binding protein (ChREBP) and its glycolytic and lipogenic target genes was abnormally elevated. Feeding, energy expenditure, and insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 60 publications
9
104
2
Order By: Relevance
“…First, Glut2 inactivation in hepatocytes of adult mice using a tamoxifen-dependent recombination system (LG2KO mice) [52] suppressed hepatic glucose uptake but did not modify glucose homeostasis in the fed, fasted, or fasted and refed states. Measurement of tissue glucose uptake in LG2KO mice showed increased uptake in the tibialis anterior and extensor digitorum longus muscles.…”
Section: Glut2 and The Hepatoportal Glucose Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…First, Glut2 inactivation in hepatocytes of adult mice using a tamoxifen-dependent recombination system (LG2KO mice) [52] suppressed hepatic glucose uptake but did not modify glucose homeostasis in the fed, fasted, or fasted and refed states. Measurement of tissue glucose uptake in LG2KO mice showed increased uptake in the tibialis anterior and extensor digitorum longus muscles.…”
Section: Glut2 and The Hepatoportal Glucose Sensormentioning
confidence: 99%
“…Indeed, since part of the glucose generated from glucose 6-phosphate in the endoplasmic reticulum can be transported back into the cytoplasm, it needs to be equilibrated with the extracellular glucose. Preventing this equilibration in LG2KO hepatocytes leads to the accumulation of glucose and glucose 6-phosphate in the cytoplasm, which causes a permanent increase in nuclear ChREBP and a paradoxical upregulation of the gene encoding L-pyruvate kinase and the lipogenic genes in the fasted state [52,53]. The presence of GLUT2 in hepatocytes is therefore required for the normal control by glucose of gene expression under physiological conditions.…”
Section: Glut2 and The Hepatoportal Glucose Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…STZ causes destruction of β-cells of the islets and reduction in insulin release (Ning et al, 2011). The structural and biochemical functions of liver and kidneys may also be affected by alteration of insulin concentration which inhibits rapid glucose uptake and storage as glycogen in liver (Seyer et al, 2013). It is well recognized that flavonoids are able to improve diabetic subject by decreasing blood glucose levels (Rauter et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…GLUT2 is also expressed in the liver and regulates glucose uptake/efflux, and this transport activity is important to maintain the blood glucose level. Recent studies demonstrated that GLUT2 also plays a key role in the preservation of beta-cell glucose competence 12) , and that a genetic variant of GLUT2 is associated with the higher intake of sugars 13) . Interestingly, the Finnish Diabetes Prevention Study showed that moderate-tovigorous physical activity could modify the risk of developing T2D associated with the genetic variant of GLUT2 in persons with impaired glucose tolerance 14) .…”
Section: Type 2 Diabetes Mellitus (T2d) and Transportersmentioning
confidence: 99%